PENGEMBANGAN BUKU AJAR ETNOMATEMATIKA BERBASIS TENUN MABUNE PADA MATERI BANGUN DATAR UNTUK SISWA KELAS IV SEKOLAH DASAR - Leu, Theresia Merlina; Koli, Radka Bodkova; Mbuik, Heryon Bernard (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study developed an ethnomathematics textbook based on Mabune weaving for teaching plane geometry to fourth-grade elementary school students. The development was motivated by the limited availability of contextual mathematics learning resources that connect geometric concepts with students’ cultural environment. The study employed a research and development design using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The product was validated by subject-matter, language, and media experts and was subsequently tested with 18 fourth-grade students at SD Negeri Nunbai. Data were collected through validation sheets, teacher and student response questionnaires, and pretest and posttest instruments. The data were analyzed descriptively using percentage scores, while learning improvement was examined using paired-samples t-test and normalized gain. The textbook achieved validity scores of 86% from the subject-matter expert, 86% from the language expert, and 91% from the media expert, all classified as highly valid. The teacher response score was 96.43%, whereas the student response score was 90.48%, indicating high practicality. The paired-samples t-test showed a statistically significant difference between pretest and posttest scores (p = .001), and the mean normalized gain was .76, categorized as high. The findings indicate that the Mabune weaving-based ethnomathematics textbook is valid, practical, and promising for supporting meaningful learning of plane geometry in elementary schools. Further research should test the product with larger and more diverse samples using a comparative design.